Synthesis and characterization of CuFe2O4/NiMgAl-LDH composite for the efficient removal of oxytetracycline antibiotic - Jamiu O. Eniola; Rajeev Kumar; Olfat A. Mohamed; A.A. Al-Rashdi; M.A. Barakat (Journal of Saudi Chemical Society)
In this study, a modified copper ferrite/NiMgAl layered double hydroxide (CuFe2O4/NiMgAl-LDH) composite was developed for the adsorptive removal of oxytetracycline hydrochloride (OTC) antibiotic from aqueous solution. Material characterization by X-ray diffraction (XRD), Scanning electron microscopy (SEM), Fourier transforms infrared spectrum (FTIR) and X-ray photoelectron spectroscopy (XPS) confirms that the resultant material composes of a hexagonal layered doubled hydroxide structure with surficial deposits on CuFe2O4 cubes. The adsorption of OTC onto the prepared materials were studied as a function of solution pH, initial OTC concentration, reaction time and temperature. The OTC adsorption capacities of the prepared materials were as follows: CuFe2O4/NiMgAl-LDH composite > NiMgAl-LDH > CuFe2O4. The adsorption of OTC in the presence of salts like CuSO4, NaHCO3, NaCl were also studied and the results revealed that CuSO4 has a positive effect on OTC adsorption while NaHCO3 and NaCl showed the neutral and antagonistic effect. The results revealed that hydrogen bonding, anionic exchange, and electrostatic forces were mainly involved in the adsorption of OTC onto CuFe2O4/NiMgAl-LDH composite. OTC adsorption followed the pseudo-second-order kinetic model while the adsorption equilibrium data were well fitted to the Langmuir isotherm model with the maximum adsorption capacity of 192 mg/g at 323K. Furthermore, the thermodynamic study revealed that the adsorption process was spontaneous and endothermic. Keywords: Adsorption, CuFe2O4 /NiMgAl-LDH composite, Oxytetracycline, Wastewater